A Description of Congenital Anomalies Among Infants in Entebbe, Uganda - Ndibazza, Juliet; Lule, Swaib; Nampijja, Margaret; Mpairwe, Harriet; Oduru, Gloria; Kiggundu, Molly; Akello, Miriam; Muhangi, Lawrence; Elliott, Alison M. (Clinical and Molecular Teratology, 2011)
Data on congenital anomalies from developing countries of the sub-Saharan region are scarce. However, it is important to have comprehensive and reliable data on the description and prevalence of congenital anomalies to allow surveillance and the implementation of appropriate public health strategies for prevention and management. In this study, we describe the profile of congenital anomalies seen in a birth cohort in Entebbe, Uganda. Congenital anomalies were defined as any structural defect present at birth. Pregnant women were recruited to the cohort between 2003 and 2005. Defects present at birth were recorded by the midwife at delivery and by physicians at the routine six-week postnatal visit and at illness-related visits until 1 year of life. The anomalies were classified by organ system according to the 10th version of the World Health Organization International Classification of Diseases (ICD-10). RESULTS: There were 180 infants with a congenital anomaly among 2365 births. The most commonly affected systems were the musculoskeletal (42.7 per 1000 births) and skin (16.1 per 1000 births). The prevalence of major anomalies was 20.3 per 1000 births; 1.7 per 1000 births for cardiac anomalies and 1.3 per 1000 births for neural system anomalies. Forty (22%) of the congenital anomalies were identified at birth, 131 (73%) at the 6- week postnatal visit, and nine (5%) at illness-related visits. Congenital anomalies are common in developing countries. Establishment of comprehensive databases for surveillance would be helpful for surveillance of effects of new exposures, for prevention, management, and health care planning. Birth Defects Research (Part A) 91:857–861, 2011. 2011 Wiley-Liss, Inc.
Keywords: Congenital anomalies; infants; epidemiology; Uganda; Africa